DISEMINASI PENGGUNAAN DANA DESA TANPA INDIKASI TINDAK PIDANA KORUPSI MENUJU DESA WISATA - Andreas Lumme (Batara Wisnu : Indonesian Journal of Community Services, 2023)
Village funds are funds used to finance governance, development implementation, community development, and community empowerment. However, it is inevitable that village funds are misused and lead to corruption. Therefore, dissemination or socialization on the use of village funds without indications of corruption is needed. This activity aims to increase the sensitivity of the village community and village officials to prevent corruption of village funds. This dissemination/socialization has motivated and raised local people's awareness of the importance of participation and supervision of the use of village funds. The principles of managing and using village funds in an orderly manner, complying with the provisions of laws and regulations, efficient, economical, effective, transparent, and responsible are the keys to preventing corruptive behavior towards village funds. The application of this principle is also an excellent means to develop a basin/village into a tourist village using a budget, which comes from village funds